Pengaruh Faktor Keterampilan Kerja, Motivasi dan Disiplin Kerja Terhadap Kinerja Pegawai pada Kantor Dinas Tenaga Kerja Kab. Labuhanbatu - Indra, Aulia (Jurnal Manajemen Akuntansi (JUMSI), 2024)
This study aims to determine the influence of factors of skill, motivation and work discipline on employee performance at the Labuhanbatu District Labor Office. This Type Of Research Is Associative Research. Data collection in this study was conducted through a survey approach with the type of quantitative descriptive research by distributing questionnaires to 48 respondents, while the population used in this study is the employee on the performance of employees at the Office of Labor Labuhanbatu district data collection techniques were conducted by interviews, questionnaires and documentation studies. Data analysis tools used in this study using SPSS (Statistical Product Sofware Solution). Data analysis techniques in this study are descriptive analysis, multiple linear regression analysis, hypothesis testing using partial significant Test (t test), simultaneous significant test (F test), and testing the coefficient of determination (R2). The results of this study showed partially (t test) it is known that the skills significantly affect the performance of employees at the Labuhanbatu District Labor Office. Motivation significant effect on employee performance on employee performance at the Labor Office of Labuhanbatu then work discipline significant effect on employee performance on employee performance at the Labor Office of Labuhanbatu on simultaneous testing (test F) it is known that motivation skills and work discipline significant effect on employee performance at the Labor Office of Labuhanbatu through testing coefficient of determination (R Square) 69.9% , and work discipline has a significant effect on employee performance 3.83% the remaining 3.25% is influenced by other factors.